Genomic Analysis of Mic1 Reveals a Novel Freshwater Long-Tailed Cyanophage - Yang, Feng; Jin, Hua; Wang, Xiao-Qian; Li, Qiong; Zhang, Jun-Tao; Cui, Ning; Jiang, Yong-Liang; Chen, Yuxing; Wu, Qing-Fa; Zhou, Cong-Zhao; Li, Wei-Fang (Frontiers in Microbiology, 2020)
Lake Chaohu, one of the five largest freshwater lakes in China, has been suffering from severe cyanobacterial blooms in the summer for many years. Cyanophages, the viruses that specifically infect cyanobacteria, play a key role in modulating cyanobacterial population, and thus regulate the emergence and decline of cyanobacterial blooms. Here we report a long-tailed cyanophage isolated from Lake Chaohu, termed Mic1, which specifically infects the cyanobacterium Microcystis aeruginosa. Mic1 has an icosahedral head of 88 nm in diameter and a long flexible tail of 400 nm. It possesses a circular genome of 92,627 bp, which contains 98 putative open reading frames. Genome sequence analysis enabled us to define a novel terminase large subunit that consists of two types of intein, indicating that the genome packaging of Mic1 is under fine control via posttranslational maturation of the terminase. Moreover, phylogenetic analysis suggested Mic1 and mitochondria share a common evolutionary origin of DNA polymerase γ gene. All together, these findings provided a start-point for investigating the co-evolution of cyanophages and its cyanobacterial hosts.